Application of integrated fuzzy-AHP for design evaluation in product development - Nurul Arifah, Che Ropa (2016)
The evaluation process of conceptual design alternatives in a new product development environment is a critical point for companies who operate in fast-growing markets. Various methods exist that are able to successfully carry out this difficult and time-consuming process. One of these methods, the Analytical Hierarchy Process (AHP) that been widely used to solve multiple-criteria decision making problems in both academic research and in industrial practice. However, due to vagueness and uncertainty in the decision-maker’s judgment, pair-wise comparison with Integrated Fuzzy-AHP may be able to accurately capture the decision-maker’s judgment. Therefore, fuzzy is introduced into the pair-wise comparison in the AHP to compensate for this deficiency in the integrated Fuzzy-AHP. This is referred to as integrated fuzzy-AHP. In this paper, a fuzzy-AHP method is used to reduce a set of conceptual design alternatives by eliminating those whose scores are smaller than a predetermined constant value obtained under certain circumstances. Then, simulation analysis is integrated with the fuzzy-AHP method. Finally, the results of integrated fuzzy- AHP are used for Preference Ratio analysis to reach to the final alternative.